TANGGUNG JAWAB HUKUM BAGI NOTARIS YANG DIJATUHI PIDANA TERHADAP BERKAS YANG MASIH DIPROSES - Muhammad Yuhdi Ilhaqh; Suprayitno, Mahmud Mulyadi, Marlina (INTELIGENSIA MEDIA, 2024)
A notary is a public official who has the authority to make authentic deeds in accordance with Article 1 number 1 of Law Number 30 of 2004 concerning the position of notary (UUJN). Notaries who violate statutory provisions must be held civilly, administratively or criminally responsible according to their actions. Article 13 UUJN only regulates the dishonorable dismissal of Notaries who have been sentenced to permanent legal penalties of more than 5 years or more, whereas Notaries who have been detained or sentenced to less than 5 years can be temporarily dismissed and submission of the notary protocol can only be handed over to the appointed Notary in the event of dismissal. while more than 3 months according to Article 63 paragraph (3) UUJN. The type of research used in this research is normative, this research is analytical descriptive. The data used to answer the problems in the research are secondary data sources. Data collection was carried out using library research. This research used qualitative data analysis. For a Notary who is being sentenced to a crime or is undergoing a period of temporary suspension, the Notary is not authorized to carry out his duties and position so that the file/deed cannot be made and if it is made then the file/deed will be invalid because the authority of the notary is revoked. The authority and position of a Notary who has been temporarily suspended can be restored and returned to being a Notary and carry out his/her position if the temporary suspension period has ended, this is in accordance with Article 10 paragraph (2) UUJN. The authority and position of a notary who is a suspect in a criminal case is not necessarily suspended forever. However, it is best as a notary to carry out his duties honestly and follow both UUJN and applicable regulations. There needs to be clearer regulations regarding files that are still being processed if the notary is sentenced to a crime. It would be good if the notary with suspect status is given a temporary suspension, even if it does not reach 3 months, so that the notary becomes more careful in carrying out his duties.